Improved growth, tolerance and intake with an extensively hydrolysed peptide feed in infants with complex disease. Issue 3 (June 2018) - Smith, Chris; McCabe, Helen; Macdonald, Sarah; Morrison, Lara; Prigg, Ruth; Trace, Sarah; Livingstone, Jennifer; Callan, Julia; Cotton, Jacqui; Hubbard, Gary; Stratton, Rebecca J.
Summary: Background & aims: Infants with complex medical conditions often display faltering growth due to elevated nutritional requirements, poor intake and intolerance of feeding with malabsorption and maldigestion. As a result their nutritional management can be extremely challenging and enteral nutritional support is required. This study aimed to investigate the effectiveness, tolerance and acceptability of nutritional support with a specially formulated, paediatric peptide feed in infants with complex disease and signs of growth faltering with their current nutritional management. Methods: This prospective intervention study investigated gastrointestinal (GI) tolerance, nutritional intake and compliance with feeding, anthropometry and growth in 18 infants (mean age 6.11 months ± 4.69, mean weight 4.97 kg ± 1.71) during 28 days of enteral nutritional support with a paediatric (1 kcal/ml) readymade peptide feed. Results: GI tolerance to nutritional support with a peptide enteral feed was good and either improved or remained stable over the study. Compliance was excellent (94.0% ± 12.6), total energy intake improved (+23 ± 42 kcal/kg, p = 0.037) and mean weight (0.61 kg ± 0.31, p  = 0.0001), length (1.89 ± 1.77 cm, p  = 0.0001), head circumference (1.33 ± 1.29 cm, p  = 0.001), weight for length Z score ( p  < 0.05), and weight for age Z score ( p  < 0.05) significantly improved. Sixty one percent (n = 11) of the infants showed signs of increased growth velocity, moving upwards in terms of their centiles. All 18 infants continued with the paediatric, peptide enteral feed once the study was complete. Conclusions: This prospective study showed that nutrition support with a specially formulated, paediatric peptide readymade feed was well tolerated, helped to promote growth, and can be considered suitable for use in infants with complex disease and faltering growth who are unable to tolerate a whole protein feed.